WD40-domain protein GORI is an integrative scaffold that is required for pollen tube growth in rice - Yu-Jin Kim; Ki-Hong Jung (Plant Signaling & Behavior, 2023)
The pollen tube plays a critical role in angiosperm plants by delivering sperm gametes for double fertilization. Although the molecular mechanisms underlying pollen tube germination and growth are crucial to crop plants, they are poorly understood. Here, we describe recent advancements in the understanding of the role of the WD40-domain protein in regulating pollen germination and discuss future directions to investigate its role in rice. GORI encodes a seven-WD40-motif protein that interacts with an AP180 N-terminal homology (ANTH)-domain protein, which modulates clathrin-mediated endocytosis (CME), and regulates Rac6 activity in the apical plasma membrane of elongating pollen tubes. Loss of function of GORI or Rac6 reduces pollen germination and tube growth, thereby resulting in male sterility in rice. In contrast, overexpression of Rac6 increases pollen tube elongation, with this effect being rescued by GORI overexpression. In the absence of ANTH, pollen germination was reduced, similar to the results observed after inhibitor treatment, indicating that pollen germination partially requires CME. Our findings demonstrated that the GORI protein is a positive regulator of pollen germination and tube growth, serving as a link between Rac6 activity regulation and ANTH-mediated endocytosis.